Mechanisms of deep brain stimulation for obsessive compulsive disorder: effects upon cells and circuits - Bourne, Sarah K.; Eckhardt, Christine A.; Sheth, Sameer A.; Eskandar, Emad N. (Frontiers in Integrative Neuroscience, 2012)
Deep brain stimulation (DBS) has emerged as a safe, effective, and reversible treatment for a number of movement disorders. This has prompted investigation of its use for other applications including psychiatric disorders. In recent years, DBS has been introduced for the treatment of obsessive compulsive disorder (OCD), which is characterized by recurrent unwanted thoughts or ideas (obsessions) and repetitive behaviors or mental acts performed in order to relieve these obsessions (compulsions). Abnormal activity in cortico-striato-thalamo-cortical (CSTC) circuits including the orbitofrontal cortex (OFC), anterior cingulate cortex (ACC), ventral striatum, and mediodorsal (MD) thalamus has been implicated in OCD. To this end a number of DBS targets including the anterior limb of the internal capsule (ALIC), ventral capsule/ventral striatum (VC/VS), ventral caudate nucleus, subthalamic nucleus (STN), and nucleus accumbens (NAc) have been investigated for the treatment of OCD. Despite its efficacy and widespread use in movement disorders, the mechanism of DBS is not fully understood, especially as it relates to psychiatric disorders. While initially thought to create a functional lesion akin to ablative procedures, it is increasingly clear that DBS may induce clinical benefit through activation of axonal fibers spanning the CSTC circuits, alteration of oscillatory activity within this network, and/or release of critical neurotransmitters. In this article we review how the use of DBS for OCD informs our understanding of both the mechanisms of DBS and the circuitry of OCD. We review the literature on DBS for OCD and discuss potential mechanisms of action at the neuronal level as well as the broader circuit level.